2013
DOI: 10.1128/jcm.00898-13
|View full text |Cite
|
Sign up to set email alerts
|

Surface Microbes in the Neonatal Intensive Care Unit: Changes with Routine Cleaning and over Time

Abstract: Premature infants in neonatal intensive care units (NICUs) are highly susceptible to infection due to the immaturity of their immune systems, and nosocomial infections are a significant risk factor for death and poor neurodevelopmental outcome in this population. To investigate the impact of cleaning within a NICU, a high-throughput short-amplicon-sequencing approach was used to profile bacterial and fungal surface communities before and after cleaning. Intensive cleaning of surfaces in contact with neonates d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
72
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 33 publications
8
72
1
Order By: Relevance
“…Four studies examined several aspects of the NICU environment in an effort to better understand how they might impact the infant microbiome. 16,29,30,34 Specific measures utilized within these studies included sampling before and after cleaning with antibacterial wipes, 16 cold versus warm spot sampling in incubators, 34 predominant NICU organisms living within specific nurseries regardless of routine cleaning and hand washing, 29 and lack of hand washing and routine cleaning before and after implementing standard precautions. 30 Microbiome samples of environmental surfaces revealed complex and diverse environments and included species associated with nosocomial infections common in the neonatal population.…”
Section: Data Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies examined several aspects of the NICU environment in an effort to better understand how they might impact the infant microbiome. 16,29,30,34 Specific measures utilized within these studies included sampling before and after cleaning with antibacterial wipes, 16 cold versus warm spot sampling in incubators, 34 predominant NICU organisms living within specific nurseries regardless of routine cleaning and hand washing, 29 and lack of hand washing and routine cleaning before and after implementing standard precautions. 30 Microbiome samples of environmental surfaces revealed complex and diverse environments and included species associated with nosocomial infections common in the neonatal population.…”
Section: Data Synthesismentioning
confidence: 99%
“…Every NICU has its own genera of microbes which can include commensal and pathogenic organisms. 16,17 With the NICU genera as the context for microbiome development, the infant’s ongoing interaction with multiple healthcare providers and caregiving processes have the potential to impact microbial colonization. A recent study showed that the risk of acquiring nasal colonization with coagulase-negative Staphylococcus (CoNS) for all neonates admitted in a NICU was 55.9%.…”
mentioning
confidence: 99%
“…Studies of the built environment have sought to understand how building architecture and engineering, in conjunction with human behavior, may influence the microbes that we encounter during our time spent indoors (which represents 87% of our time on average [8]). Such studies have aimed at capturing the microbial communities associated with both air and surfaces in homes (9, 10), hospitals (11, 12), classrooms (13), offices (14, 15), and restrooms (16), as well as community assemblages within plumbing systems (1719) and an expanding set of other indoor microhabitats.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of surfaces and their cleaning for controlling outbreaks of specific organisms and eradicating sources of potential pathogens in NICUs has been highlighted in a few prior studies [9][10][11]. Other NICU environmental parameters previously studied in relation to prevention of nosocomial infections have included noise, illumination, medical equipment hygiene, microbes on surfaces, overcrowding, and the importance of inhibiting free mixing across rooms [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%